Nonlinear seismic response of a base isolated single pylon cable-stayed bridge - Han, Q.; Wen, J.; Du, X.; Zhong, Z.; Hao, Hong (Pergamon, 2018)
The vulnerability of single pylon cable-stayed bridges under strong ground motions are of great concern to both researchers and engineers. This paper investigates the seismic performance of reinforced concrete (RC) single pylon cable-stayed bridge equipped with friction sliding bearings under bi-directional earthquake excitations. Three-dimensional numerical models, consisting of the dynamic p-y elements, the fiber elements and the multi-layer shell elements, were developed in this study based on the prototype of a single pylon cable-stayed bridge in Guizhou Province, China, to investigate its seismic response. Three different types of friction sliding bearings were implemented between the base of the RC pier and the pile foundation to mitigate the dynamic response of the bridge superstructure under strong ground motions. The results of the nonlinear time history analyses indicate that friction sliding bearings can effectively reduce the base shear and the bending moment of the RC pier, as well as the seismic responses of substructure, at the cost of increasing the absolute displacement of the deck. To reduce the deck displacement, viscous dampers were implemented in parallel to the friction sliding bearings. Parametric studies and optimization analyses were performed on the critical parameters of the viscous dampers with the target of minimizing the absolute displacement of the deck and reducing the base shear of the RC pier to an acceptable level. The numerical results show that implementation of friction sliding bearings together with the viscous dampers is an effective seismic control approach to mitigate the seismic damage of the single pylon cable-stayed bridge.